2016
DOI: 10.1016/j.ijheh.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and persistence of faecal bacterial and viral indicators in Mytilus edulis and Crassostrea gigas

Abstract: This study investigated the response of two shellfish species -mussels (Mytilus edulis) and oysters (Crassostrea gigas) to microbial contamination in order to gain a better understanding of the bioaccumulation and persistence of microorganisms under controlled conditions. M. edulis and C. gigas were placed in sterile laboratory-prepared artificial seawater and initial tests were carried out to ensure both faecal indicator bacteria (FIB) and bacteriophages were below detection limits. FIB and phages were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…In this study, the decreased kinetics of GI and GII NoV (genomes) and FRNAPH (infectious particles and genomes) in oysters under different purification conditions were established. When focusing only on purification conditions applied to oysters coming from polluted areas, many studies have shown not only the incidence of physicochemical conditions (i.e., water temperature, salinity, and dissolved oxygen) on shellfish physiology but also the effect of the initial microorganism load (i.e., natural or artificial contamination) (10,(35)(36)(37). For these reasons, we decided to work with naturally NoV-contaminated oysters that were also positive for FRNAPH, because of the high correlation previously demonstrated (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the decreased kinetics of GI and GII NoV (genomes) and FRNAPH (infectious particles and genomes) in oysters under different purification conditions were established. When focusing only on purification conditions applied to oysters coming from polluted areas, many studies have shown not only the incidence of physicochemical conditions (i.e., water temperature, salinity, and dissolved oxygen) on shellfish physiology but also the effect of the initial microorganism load (i.e., natural or artificial contamination) (10,(35)(36)(37). For these reasons, we decided to work with naturally NoV-contaminated oysters that were also positive for FRNAPH, because of the high correlation previously demonstrated (25).…”
Section: Discussionmentioning
confidence: 99%
“…When the focus was only on the depuration conditions applied to oysters coming from polluted areas, many studies have shown not only the impact of the physicochemical conditions (i.e., water temperature, salinity, dissolved oxygen) and shellfish physiology but also the impact of the initial microorganism load (i.e., natural or artificial contamination) (59)(60)(61)(62). For these reasons, we decided to work with oysters that were naturally contaminated with NoV and that were also positive for FRNAPH because of the high correlation of the presence of the two viruses discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the result of differences in the physiology of the shellfish or the pathogen, the rate of metabolism in the shellfish, the duration of exposure of the shellfish to the pathogen or its source, the exposure dose and other factors, such as salinity and temperature, which all serve to influence filtration rates within the shellfish (Olalemi et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This work is applicable to other types of shellfish species, although different shellfish species may demonstrate varying abilities to bioaccumulate microbial indicators or pathogens. This may be the result of differences in the physiology of the shellfish or the pathogen, the rate of metabolism in the shellfish, the duration of exposure of the shellfish to the pathogen or its source, the exposure dose and other factors, such as salinity and temperature, which all serve to influence filtration rates within the shellfish (Olalemi et al 2016).…”
Section: Discussionmentioning
confidence: 99%